Writing Africa in the short story - Emenyo̲nu, Ernest, 1939-; Cambridge eBooks (Suffolk : Boydell & Brewer, 2013)
African writers have, much more than the critics, recognized the beauty and potency of the short story. Always the least studied in African literature classrooms and the most critically overlooked genre in African literature today, the African short story is now given the attention it deserves. Contributors here take a close look at the African short story to re-define its own peculiar pedigree, chart its trajectory, critique its present state and examine its creative possibilities. They examine how the short story and the novel complement each other, or exist in contradistinction, within the context of culture and politics, history and public memory, legends, myths and folklore. Ernest Emenyonu is Professor of Africana Studies at the University of Michigan-Flint, USA; the editorial board is composed of scholars from US, UK and African universities. Nigeria: HEBN
'Once upon a time begins a story ... ' / Ernest N. Emenyou -- 'Real Africa'/'Which Africa?' : the critique of mimetic realism in Chimamanda Ngozi Adichie's short fiction / Eve Eisenberg -- Writing apartheid: Miriam Tlali's Soweto Stories / Mary Jane Androne -- Articulations of home & Muslim identity in the short stories of Leila Aboulela / Lindsey Zanchettin -- Ugandan women in contest with reality : Mary K. Okurutu's A Woman's voice & the women's future / Iniobong I. Uko -- Snapshots of the Botswana nation : Bessie Head's The Collector of treasures & other Botswana Village tales as a national project / Louisa Uchum Egbunike -- Widowhood : institutionalized dead weight to personal identity & dignity : a reading of Ifeoma Okoye's The Trial & other stories / Regina Okafor -- Feminist censure of marriage in Islamic societies : a thematic analysis of Alifa Rifaat's short stories / Juliana Daniels -- Diaspora identities in short fiction by Chimamanda Ngozi Adichie & Sefi Atta / Rose A. Sackeyfio -- Exposition of apartheid South African violence & injustice in Alex Ia Guma's short stories / Blessing Diala-Ogamba -- Locating a genre: is Zimbabwe a short story country? / Tinashe Mushakavanhu -- Mohammed Dib's short stories on the memory of Algeria / Imene Moulati -- Ama Ata Aidoo's short stories : empowering the African girl-child / Hellen Roselyne Shigali -- Ama Ata Aidoo : an interview for ALT / Maureen Eke, Vincent Odamtten & Stephanie Newell.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Short stories, African (English) -- History and criticism; Electronic books